Histological description of hepatopancreas in spiny lobster (Panulirus penicillatus) and bamboo lobster (Panulirus versicolor) in Sabang Waters, Aceh, Indonesia - MUHAMMADAR ABDULLAH ABBAS; MUHAMMAD IQBAL; FIRDUS FIRDUS; WIDYA SARI; DEDI FAZRIANSYAH PUTRA (Society for Indonesian Biodiversity, 2024)
Abstract. Abbas MA, Iqbal M, Firdus F, Sari W, Putra DF. 2024. Histological description of hepatopancreas in spiny lobster (Panulirus penicillatus) and bamboo lobster (Panulirus versicolor) in Sabang Waters, Aceh, Indonesia. Biodiversitas 25: 3739-3749. This study aimed to analyze the histology of the hepatopancreas in two lobster species, Panulirus penicillatus (Olivier, 1791) and Panulirus versicolor (Latreille, 1804), originating from Sabang waters. The primary objectives were to identify and compare the cellular composition and structural differences within the hepatopancreas of both species and to understand how these differences might reflect adaptations to their distinct local environments and dietary conditions. The histological analysis was conducted on the hepatopancreas of 10 specimens from each species using the paraffin section method and Hematoxylin-Eosin (H&E) staining. The results showed striking differences in the tubule cells between the two species. In P. penicillatus, B-cells were found to be more dominant, whereas in P. versicolor, F-cells were more prevalent. Additionally, the study observed significant variations in the size and arrangement of the Tubules, as well as the distribution of different cell types within the hepatopancreas. These differences likely reflect adaptations to their distinct local environments and dietary conditions in Sabang waters. The hepatopancreas, a vital organ for digestion, nutrient absorption, and detoxification, showed distinct histological features in the two lobster species. Understanding these variations provides valuable insights into their biological and physiological adaptations. The research highlights the importance of species-specific studies to comprehend the ecological and physiological adaptations of marine organisms. Furthermore, these findings have significant practical implications for the management and cultivation of these lobster species. By understanding the histological differences and their underlying causes, better strategies can be developed for the conservation and sustainable exploitation of these valuable marine resources. The study underscores the role of histological analysis in assessing the health and condition of lobster populations, which is crucial for effective management.